Cross-species infection potential of avian influenza H13 viruses isolated from wild aquatic birds to poultry and mammals. Issue 1 (31st December 2023) - Sun, Weiyang; Zhao, Menglin; Yu, Zhijun; Li, Yuanguo; Zhang, Xinghai; Feng, Na; Wang, Tiecheng; Wang, Hongmei; He, Hongbin; Zhao, Yongkun; Yang, Songtao; Xia, Xianzhu; et al.
ABSTRACT: Wild aquatic birds are the primary hosts of H13 avian influenza viruses (AIVs). Herein, we performed a genetic analysis of two H13 AIVs isolated from wild birds in China and evaluated their infection potential in poultry to further explore the potential for transmission from wild aquatic birds to poultry. Our results showed that the two strains belong to different groups, one strain (A/mallard/Dalian/DZ-137/2013; abbreviated as DZ137) belongs to Group I, whereas the other strain (A/Eurasian Curlew/Liaoning/ZH-385/2014; abbreviated as ZH385) belongs to Group III. In vitro experiments showed that both DZ137 and ZH385 can replicate efficiently in chicken embryo fibroblast cells. We found that these H13 AIVs can also efficiently replicate in mammalian cell lines, including human embryonic kidney cells and Madin-Darby canine kidney cells. In vivo experiments showed that DZ137 and ZH385 can infect 1-day-old specific pathogen-free (SPF) chickens, and that ZH385 has a higher replication ability in chickens than DZ137. Notably, only ZH385 can replicate efficiently in 10-day-old SPF chickens. However, neither DZ137 nor ZH385 can replicate well in turkeys and quails. Both DZ137 and ZH385 can replicate in 3-week-old mice. Serological surveillance of poultry showed a 4.6%-10.4% (15/328-34/328) antibody-positive rate against H13 AIVs in farm chickens. Our findings indicate that H13 AIVs have the replication ability in chickens and mice and may have a risk of crossing the host barrier from wild aquatic birds to poultry or mammals in the future.